Was the German Battlefleet Programme the Main Reason for the End of Britain’s “Splendid Isolation”? - Nathan Brewster (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2020)
This historiographical essay challenges the common historical narrative that Britain left 'splendid isolation' as a result of perceived German aggression - particularly considering Germany's battlefleet programme. Investigating closer Anglo-American ties, the Anglo-Japanese agreement and the Entente Cordiale show that Britain started to abandon an isolationist policy due to its vast, global and often burdensome empire before the German battlefleet started to present itself as a problem. Rather than pinning Britain's alliances at the turn of the twentieth-century on one factor in Europe, this essay investigates the impact the Americas, Africa, Central Asia and the Far East had on Britain's changing international position.
Keywords: German battlefleet; splendid isolation; alliance system; Britain and France; Britain and Germany; Anglo-Japanese agreement; Entente Cordiale; Britain and Japan